Online food ordering & delivery service: a study of satisfaction among students residing in UiTM Pulau Pinang during Movement Control Order (MCO) / Fairuz Ahmad Faizar, Najua Mohd Ali and Siti Anis Adilah Tarmazi - Faizar, Fairuz Ahmad; Mohd Ali, Najua; Tarmazi, Siti Anis Adilah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Because of the ease, cost and variety of cuisines offered; the distribution of food service through online food industry has evolved at an unprecedented rate all over the world (Dsouza & Sharma, 2020). In this pandemic, Movement Control Order (MCO) has been provided by the government for citizens to obey. One of the significant services has been food distribution. The MCO has helped to raise customer awareness and acceptance of online food delivery services. However, with the advent of the Online to Offline (O2O) era, the rise of various food delivery platforms not only provides consumers with more choices, but also allows restaurant operators to reach more potential consumers and increase their additional revenue thus; making rooms for research to be done in accessing factors affecting satisfaction level among customers. Thus, the purpose of this study is to investigate the consumers' level of satisfaction towards online food delivery service. A quantitative study has been through with 215 respondents ranging from diploma and degree students' residing in UiTM Permatang Pauh & Bertam campus was chosen as sample. A correlation analysis was conducted to determine the strength of the linear correlation between variables. The finding revealed that quality, price and ease of use have a positive relationship towards satisfaction of using the online food delivery ordering service. From the findings it are often concluded that satisfaction towards the online food delivery services will significantly vary based from quality of food ordered or received, hygienic value of the delivery process, and price of food ordered online as well as the ease of use of the online food delivery services apps or platform.